The Contribution Of The Philosophy Of Science In Research Science And Social Life - Fatonah Fatonah; Ismail Ismail; Teguh Adimarta; Mar’atun Sholiha; Rafik Darmansyah; Fardinal Fardinal; Yanfaunnas Yanfaunnas; Bimo Tunggal Prastetyo; Risatri Gusmahansyah (Dinasti International Journal of Management Science, 2022)
This article reviews the Contribution of the Philosophy of Science in Scientific Research and Social Life, which is a form of qualitative research and literature study or Philosophy of Science library research. The results of this literature review article show that: (1) History records that philosophy has bridged the change from mythcentric to logocentric, the change from thinking patterns based on myth and superstition to thinking patterns based on science (logos). This change in mindset has proven to have far-reaching implications for civilization. Nature and its phenomena that were previously feared are then studied, researched, and even exploited. From these investigations of natural phenomena, various theories and scientific findings were found that explain the changes and phenomena that occur, both in the universe (macrocosm) and in the human world (microcosm). (2) The influence of knowledge in the course of philosophical life from century to century, from myth, anthropos, and then to theos (theology/dogma) and changed to logos. That is the journey of the philosophy of knowledge to become a philosophy of science which later gave birth to the sciences of astronomy, cosmology, physics, chemistry, and so on. Meanwhile, from the investigation of the human microcosm, the sciences of biology, psychology, sociology, and so on have developed. Over time, these sciences have developed to become more specialized and increasingly produce technologies that have a direct and broad impact on civilization and human life. (3) The philosophy of science itself contributes to scientific inquiry and in human life, especially These sciences then develop into more specialized and increasingly produce technologies that have a direct and broad impact on civilization and human life. (3) The philosophy of science itself contributes to scientific inquiry and in human life, especiallyknowledge in the form of deductive reasoning related to empirical and positivist (qualitative) and inductive reasoning with rationalism, constructivist and critical (qualitative). Although rationally science compiles its knowledge consistently and cumulatively, empirically science separates knowledge that is in accordance with facts and that which is not. Therefore, before being empirically verified, all rational explanations put forward are only hypothetical. (4) In addition, the philosophy of science has also substantially, methodically and relevantly provided a new paradigm in scientific research as well as for human life, namely; Positivism Paradigm, Constructivist Paradigm, and Critical Paradigm. These three paradigms are very important for a researcher who will compose a scientific work, be it a thesis, thesis or dissertation or other scientific paper.